Investigating cestode modulation of host neuronal excitability and cell-type-specific gene expression in an in vitro mouse model of neurocysticercosis - Steyn, Teresa (Department of Human Biology, 2024)
Neurocysticercosis (NCC), caused by Taenia solium larvae, is the leading helminthic brain infection in humans, with epilepsy as its most common manifestation. Interestingly, seizures are rare during early stages when viable larvae are thought to suppress host inflammation. Seizures tend to occur when larvae die and immune suppression ceases, which has led to the hypothesis that the host's immune response contributes to seizures in NCC. Further research is required to better understand the effects that immune activation and Taenia larvae have in the brain. In this thesis, I exposed mouse hippocampal organotypic brain slice cultures (OBSCs) to lipopolysaccharide (LPS) and a Taenia crassiceps homogenate and used singlenucleus RNA sequencing and whole-cell patch-clamp electrophysiology to investigate potential links between inflammation and network excitability at a transcriptomic and electrophysiological level. In the first part of the thesis, I found that while LPS significantly affected cell-type specific gene expression associated with inflammatory pathways, it had little impact on genes modulating neuronal excitability. This was corroborated by whole-cell patchclamp data demonstrating no LPS-induced changes in the intrinsic electrical properties of pyramidal neurons. In the second part of the thesis, I exposed mouse hippocampal OBSCs to a T. crassiceps homogenate alone or in combination with LPS to evaluate its immunomodulatory activity. The T. crassiceps homogenate blocked the induction of pro-inflammatory transcriptional activity across different cell types when added to LPS. This suggested that it likely acts up-stream of the toll-like receptor 4 proinflammatory cascade. The homogenate had minimal influence on the expression of neuronal excitability genes, and whole-cell patch-clamp experiments confirmed no significant differences in pyramidal neuron electrical properties among the treatment groups. My data indicate that both LPS and a homogenate made from viable Taenia larvae drive cell-type-specific immunomodulatory changes but have limited effects on basic neuronal excitability, at least over a relatively short period of exposure and in the absence of an adaptive immune response. My findings are relevant for understanding how Taenia larvae and inflammatory responses relate to the emergence of seizures in NCC.